The Effect of Internal Control, Implementation of Good Governance, and Organizational Commitment on Employee Performance : (Study at the Jambi Province Industry and Trade Office) - Syahrani, Adinda Putri; Gowon, Muhammad; Hernando, Riski (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2024)
This study aims to determine the effect of the application of internal control, good governance, and organizational commitment to on employee performance at the Department of Industry and Trade of Jambi Province. The type of research used in this study is a type of quantitative research. The data used is primary data in the form of a research questionnaire. The population in this study were employees who worked at the Industry and Trade Office of Jambi Province. This study used a purposive sampling technique. The results of the questionnaire data were analyzed and processed using the WarpPLS 7.0 application. The results of this study each variable has an influence on employee performance.This study uses the warp pls 7.0 application as a tool for processing data. while previous studies used SPSS to process data.